Reversible cerebral vasoconstriction syndrome and dissection in the setting of COVID-19 infection - Dakay, Katarina (J Stroke Cerebrovasc Dis, 2020)
The current COVID-19 pandemic has recently brought to attention the myriad of neuro- logic sequelae associated with Coronavirus infection including the predilection for stroke, particularly in young patients. Reversible cerebral vasoconstriction syndrome (RCVS) is a well-described clinical syndrome leading to vasoconstriction in the intracra- nial vessels, and has been associated with convexity subarachnoid hemorrhage and oc- casionally cervical artery dissection. It is usually reported in the context of a trigger such as medications, recreational drugs, or the postpartum state; however, it has not been described in COVID-19 infection. We report a case of both cervical vertebral ar- tery dissection as well as convexity subarachnoid hemorrhage due to RCVS, in a pa- tient with COVID-19 infection and no other triggers.